Gp85 protein encapsulated by alginate-chitosan composite microspheres induced strong immunogenicity against avian leukosis virus in chicken - Lei, Tianyu; Liu, Rongchang; Zhuang, Liyun; Dai, Tingting; Meng, Qingfu; Zhang, Xiaodong; Bao, Yinli; Huang, Cuiqin; Lin, Weiming; Huang, Yu; Zheng, Xintian (Frontiers in Veterinary Science, 2024)
Introduction Avian leukosis, a viral disease affecting birds such as chickens, presents significant challenges in poultry farming due to tumor formation, decreased egg production, and increased mortality. Despite the absence of a commercial vaccine, avian leukosis virus (ALV) infections have been extensively documented, resulting in substantial economic losses in the poultry industry. This study aimed to develop alginate-chitosan composite microspheres loaded with ALV-J Gp85 protein (referred to as aCHP-gp85) as a potential vaccine candidate. Methods Sodium alginate and chitosan were utilized as encapsulating materials, with the ALV-J Gp85 protein serving as the active ingredient. The study involved 45 specific pathogen-free (SPF) chickens to evaluate the immunological effectiveness of aCHP-gp85 compared to a traditional Freund adjuvant-gp85 vaccine (Freund-gp85). Two rounds of vaccination were administered, and antibody levels, mRNA expression of immune markers, splenic lymphocyte proliferation, and immune response were assessed. An animal challenge experiment was conducted to evaluate the vaccine’s efficacy in reducing ALV-J virus presence and improving clinical conditions. Results The results demonstrated that aCHP-gp85 induced a significant and sustained increase in antibody levels compared to Freund-gp85, with the elevated response lasting for 84 days. Furthermore, aCHP-gp85 significantly upregulated mRNA expression levels of key immune markers, notably TNF-α and IFN-γ. The application of ALV-J Gp85 protein within the aCHP-gp85 group led to a significant increase in splenic lymphocyte proliferation and immune response. In the animal challenge experiment, aCHP-gp85 effectively reduced ALV-J virus presence and improved clinical conditions compared to other groups, with no significant pathological changes observed. Discussion The findings suggest that aCHP-gp85 elicits a strong and prolonged immune response compared to Freund-gp85, indicating its potential as an innovative ALV-J vaccine candidate. These results provide valuable insights for addressing avian leukosis in the poultry industry, both academically and practically.